1971
DOI: 10.1021/bi00789a024
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-catalyzed hydrogen isotope exchange at position 5 of uridine. Model for enzymic carbon alkylation reactions of pyrimidines

Abstract: H-isotope exchange inhibitor are reasonably high as early as 12 hr after birth and increase dramatically as the animal becomes an adult. The data do not eliminate the birth process itself as being the triggering mechanism, however, studies carried out with fasted animals show that it is possible to delay the appearance of inhibitor activity by withholding food from the newborn animal for at least 48 hr.Recently, Sharma and Borek (1970) have shown a tRNA methylase inhibitor to be under estradiol regulation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Uridine-5-2 H can be isolated in good yield with high isotope incorporation upon treatment with 2-mercaptoethylamine in 2 H 2 O either at room or at elevated temperature 64,65 . Similar catalytic activity has been observed for glutathione 57 and cysteine 56,61 59 upon formation of a C6 adduct with 2'-deoxyuridine monophosphate.…”
Section: Scheme 2 R = H or Ribofuranos-1-ylsupporting
confidence: 70%
See 1 more Smart Citation
“…Uridine-5-2 H can be isolated in good yield with high isotope incorporation upon treatment with 2-mercaptoethylamine in 2 H 2 O either at room or at elevated temperature 64,65 . Similar catalytic activity has been observed for glutathione 57 and cysteine 56,61 59 upon formation of a C6 adduct with 2'-deoxyuridine monophosphate.…”
Section: Scheme 2 R = H or Ribofuranos-1-ylsupporting
confidence: 70%
“…This makes the NMR spectral assignment easier for structural studies [44][45][46][47][48][49][50][51] . Base deuterated molecules can also be used in conformational investigations by Raman [52][53][54] or infrared 55 spectroscopy, in biological studies [56][57][58][59][60][61] and studies on hydroxyl radical reactions with nucleosides 62,63 .…”
Section: Deuteration Of the Aglyconementioning
confidence: 99%
“…Although model studies favoring a nucleophilic attack at the 6-position of the pyrimidine ring have been reported (7,8), the role of cysteine as a nucleophile (9) was questioned recently by Sommer and Santi (10) when they could not obtain evidence for cysteine in an FdUMP-containing peptide isolated from the synthetase. The latter finding can be questioned, in turn, as a result of prior studies with sulfhydryl inhibitors (3,5,6), which implicated a sulfhydryl group at the active site and more recent ones with a5S-labeled thymidylate synthetase (11).…”
mentioning
confidence: 99%
“…Thymidylate synthetase, a target of drugs in cancer chemotherapy [Danen- berg, 1977;Friedkin, 1973;Santi, 19801 is a good example for the operation of the principle of microscopic reversibility . Figure 9 outlines the mechanism of covalent nucleophilic catalysis of C-C bond formation, the initial sequence of a complex, multistep reaction [Benkovic and Bullard, 1973;Benkovic, 1980;Friedkin, 1973;Kalman, 1971a;Kalman, 197 lb;Pogolotti and Santi, 19771. It is also shown that an analogous reaction sequence is involved when the substrate, deoxyuridylate (dUMP) is replaced by the potent inhibitor, 5-fluoro-dUMP, the active form of the antineoplastic drugs, 5-fluoropyrimidines.…”
Section: B Stability Of Enzyme-inhibitor Complexesmentioning
confidence: 99%